CORRELATION BETWEEN TEACHERS’ PERCEPTION OF PRINCIPALS’ EFFECTIVE MANAGEMENT OF SCHOOL PLANT AND TEACHERS’ JOB INVOLVEMENT IN SECONDARY SCHOOLS IN AWKA EDUCATION ZONE (Journal of Association of Educational Management and Policy Practitioners, 2024)
The study examined the correlation between teachers‘ perception of principals‘ effective management of school plant and teachers‘ job involvement in secondary schools in Awka Education zone of Anambra State. One research question and one hypothesis guided the study. Design used for the study was correlation while the population of the study comprised all the public secondary schools in the five local government areas of Awka education zone with a total of 64 schools having 1233teachers made up of 147 males and 1086 females. Using stratified random sampling technique, 585 teachers were selected which is 47.4%. Instrument for data collection was a questionnaire type designed by the researcher and named ―Teachers‘ Perception of Principals‘ Effective Management of School Plant and Teachers‘ Job Involvement Questionnaire‖ (PPEMSPTJIQ). The instrument has two sections: Teachers‘ Perception of Principals Effective Management of School Plant Scale (TPPEMSPS) which contained 10 questionnaire items and was used to gather data on the independent variable of the study while the second section was tagged Teachers‘ Job Involvement Questionnaire (TJIQ) contained 10 questionnaire items and was used to collect data on the dependent variable of the study. The instrument was face and content validated using experts in relevant fields. The average reliability of PPEMSPTJI was 0.79 while that of TJIQ was 0.82 using Pearson Moment Correlation coefficient. The findings revealed that that a low positive relationship exists between teachers‘ perception of principals‘ effective management of school plant and teachers‘ job involvement in public secondary schools in Awka education zone of Anambra State. Based on the findings, it is recommended that enlightenment campaign be organized by relevant agencies for the principals on effective management of school plant as it relates to teachers‘ job involvement so as to encourage teachers for improved teachers‘ job involvement.